Pengembangan Media Pembelajaran Menggunakan Permainan Tic Tac Toe Pada Materi Trigonometri - Hikmah Ayu Retno; Alifa Rizka Utami; Aufadini Bunga Firmansyah (International Forum of Researchers and Lecturers, 2024)
This study aims to improve students' understanding skills in learning Mathematics, especially in Trigonometry material by using tic tac toe game-based learning media, which is called the Tic Tac Toe game. The Tic Tac Toe game is a type of tic tac toe game in which players mark the spaces in an 8×8 grid with their chips. The player who manages to place 5 tokens using the chips in a row in a horizontal, vertical or diagonal row will win the game. The Tic Tac Toe game is a fun and challenging game for students who play it. Students as players are required to answer the math questions listed on the question cards to be able to place chips into the chip spaces or boxes on the game board. The research conducted was in the form of R&D (Research and Development) development research. This research aims to develop a new product or perfect an existing product (Sugiyono, 2015). This research is an educational research and development study which aims to develop learning resources for educational games by utilizing the Tic Tac Toe game with trigonometry for class XI. The development model used by researchers is the ADDIE (Analysis-Design-DevelopmentImplementation-Evaluation) model which will be carried out in the ADDIE stages. ”. This game media consists of game boards, player chips, game cards and guidebooks. The game Tic Tac Toe is a development of the game Tic Tac Toe in general. Tic Tac Toe games usually only have a 3x3 grid, in contrast to Tic Tac Toe which presents a view with an 8x8 grid so that the scope of players can be even wider. In addition, this game media is also made with a size of 60x68 cm, accompanied by a magnetic plate on the board so that players can attach chips equipped with magnets to the game board. Another difference can be seen from the number of players who can play the game, where in the usual Tic Tac Toe game it can only be played by 2 people, while the Tic Tac Toe game can be played by more than 2 people or in groups.